2021
DOI: 10.1158/2643-3230.bcd-21-0046
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Single-Cell Proteogenomics to Distinguish Acute Myeloid Leukemia from Nonmalignant Clonal Hematopoiesis

Abstract: Genetic mutations associated with acute myeloid leukemia (AML) also occur in agerelated clonal hematopoiesis, often in the same individual. This makes confident assignment of detected variants to malignancy challenging. The issue is particularly crucial for AML posttreatment measurable residual disease monitoring, where results can be discordant between genetic sequencing and flow cytometry. We show here that it is possible to distinguish AML from clonal hematopoiesis and to resolve the immunophenotypic identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…These patients have been reported previously. 37 76 (C) Kaplan-Meier survival curve with 95% CI. (D) Summary of grades 3 and 4 adverse events and irAEs that occurred during treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients have been reported previously. 37 76 (C) Kaplan-Meier survival curve with 95% CI. (D) Summary of grades 3 and 4 adverse events and irAEs that occurred during treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the use of patient-personalized scDNA-seq on baseline samples for these two patients to resolve leukemic clonal landscape. 37 We therefore also acquired scDNA-seq with oligonucleotide-conjugated antibodies against myeloid markers on these relapse samples ( figure 6C, D ). We confirmed that the relapsing AML had the same genomic mutational features and cell-surface immunophenotype as baseline and that the HLA class I and class II of the leukemic clone remained stable at relapse compared with initial diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach is unable to target personal mutations and less frequent variants ( 98 , 99 ) that would otherwise substantially increase the resolution of leukemic evolution ( 100 , 101 ). This shortcoming can be addressed either through screening of personal mutations with WES and subsequent targeted single-cell sequencing ( 102 , 103 ), or with unbiased scWGS-seq. Similar to the analysis of CNV, a critical step in the identification of somatic nuclear mutations from scWGS-seq involves stringent filtering of false positive results ( 104 ).…”
Section: Tool Kits For Longitudinal Tracking Of Disease Evolution At the Single-cell Levelmentioning
confidence: 99%
“…Miles et al observed that CD11b expression co-occurred with sub-clones harboring a RAS mutation [ 91 ]. Another recent study explored the utility of proteogenomics in three AML patients, and concluded that it can potentially improve precision medicine in AML [ 92 ].…”
Section: Challenges Related To Mrd Detection By Ngsmentioning
confidence: 99%